House dust mold in Istanbul. II. Detection of mold species causing allergy in house dust mycological flora [Istanbul'da ev tozu küfleri uzerine calişmalar. II. Ev tozu mikolojik florasinda allerji nedeni olan küflerin tanimlanmasi.] - (:unkn) unknown (My University, 1990)
In our study mycological analyses were carried out in houses of 16 people who had history of dust allergy and asthma, 126 mould strains belonging to 63 genera and species were isolated and identified. The relationship between the house dust flora and the disease of these people was also investigated.